A clinicopathological study of sinonasal lesions-5 years study in a rural hospital setup (Journal of Pathology of Nepal, 2023)
Background: Sinonasal lesions of both non-neoplastic and neoplastic variants are frequently observed by clinicians in the nasal cavity and paranasal sinuses. Sinonasal lesions are important due to divergence in their behavior and prognosis. Hence, a careful histological workup remains the mainstay of a final definitive diagnosis and timely intervention.Materials and methods: A prospective analysis was done on 151 patients of Sinonasal masses who presented to the Department of Otorhinolaryngology, MVJ Medical College and Hospital, from 2014 to 2019. Their biodata, clinical profile, and histopathological diagnosis were analyzed.Results: Non-neoplastic lesions (135 cases, 89.4%) were more frequent than neoplastic lesions (16 cases, 10.59%), and showed male predominance with an M: F ratio of 1.7:1. Nasal polyp (119 cases, 88%) was the most common lesion. Nasal obstruction (89 cases 89.45%) was the most common presenting feature. Among the neoplastic lesions, lobular capillary hemangioma was the most common benign lesion (2 cases,50%), and squamous cell carcinoma 2 cases (18.1%), was the most common malignant lesion.Conclusions: Sinonasal masses can present with overlapping clinical features, hence, it is important to categorize them into non-neoplastic and neoplastic lesions for further management. Histopathology remains the gold standard for establishing the diagnosis in such cases.